Respuesta :

kanest
Assuming the left side is 6x^2,

Divide both sides by 6:

[tex]x^{2} = 2x - 4[/tex]

Set the equation to equal 0 by subtracting both sides by the left side:

[tex]x^{2} - 2x + 4 = 0[/tex]

Use the quadratic formula to solve for x:

[tex]x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex]

[tex]a = 1, b = -2, c = 4[/tex]

[tex]\frac{2\pm\sqrt{-2^2-4(1)(4)}}{2(1)} = \frac{2\pm\sqrt{-12}}{2}[/tex]

[tex] \frac{2\pm\sqrt{-12}}{2} = 1 - i \sqrt{3}, 1 + i\sqrt{3}[/tex]

x will equal 1 - i sqrt(3) and 1 + i sqrt(3).
ACCESS MORE